FINGERPRINT VERIFICATION SYSTEM USING PRINCIPALCOMPONENT TRANSFORMATION EIGENVECTORS TECHNIQUE - A., Fouad (Iraqi Journal of Science, 2024)
A fingerprint verification technique is presented. The Principal ComponentTransformation “PCT” is used to identify a checked person, by comparing itseigenvector with the PCT eigenvectors of stored fingerprints images in a Database.The computed Eigenvectors of the input images are determined from the covariancematrix of the set of fingerprints reduced mean images which were ascended ascolumn vectors in a two dimensional array. The covariance matrix then determinedby multiplying the mean (i.e. average) reduced matrix by its transpose. Thesimilarity between the stored images of the fingers (as Database) and the test fingeris presented by utilizing the Minimum Mean Square Error (MMSE) criterion.